Annual cycle of Scots pine photosynthesis - Hari, Pertti; Kerminen, Veli-Matti; Kulmala, Liisa; Kulmala, Markku; Noe, Steffen; Petäjä, Tuukka; Vanhatalo, Anni; Bäck, Jaana (Atmospheric Chemistry and Physics, 2017)
Photosynthesis, i.e. the assimilation of atmospheric carbon to organic molecules with the help of solar energy, is a fundamental and well-understood process. Here, we connect theoretically the fundamental concepts affecting C3 photosynthesis with the main environmental drivers (ambient temperature and solar light intensity), using six axioms based on physiological and physical knowledge, and yield straightforward and simple mathematical equations. The light and carbon reactions in photosynthesis are based on the coherent operation of the photosynthetic machinery, which is formed of a complicated chain of enzymes, membrane pumps and pigments. A powerful biochemical regulation system has emerged through evolution to match photosynthesis with the annual cycle of solar light and temperature. The action of the biochemical regulation system generates the annual cycle of photosynthesis and emergent properties, the state of the photosynthetic machinery and the efficiency of photosynthesis. The state and the efficiency of the photosynthetic machinery is dynamically changing due to biosynthesis and decomposition of the molecules. The mathematical analysis of the system, defined by the very fundamental concepts and axioms, resulted in exact predictions of the behaviour of daily and annual patterns in photosynthesis. We tested the predictions with extensive field measurements of Scots pine (Pinus sylvestris L.) photosynthesis on a branch scale in northern Finland. Our theory gained strong support through rigorous testing.